2006
DOI: 10.1099/vir.0.81999-0
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of PrPCWD accumulation during the course of chronic wasting disease infection in orally inoculated mule deer (Odocoileus hemionus)

Abstract: Patterns of abnormal prion protein (PrP) accumulation during the course of chronic wasting disease (CWD) infection were studied and the distribution and timing of disease-associated PrP (PrP CWD ) deposition and lesions in 19 mule deer (Odocoileus hemionus) 90-785 days after oral inoculation were described. PrP CWD deposition occurred relatively rapidly and widely in lymphoid tissues, later in central and peripheral nervous tissues and sporadically in a variety of tissues and organs in terminal disease stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
183
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(202 citation statements)
references
References 46 publications
19
183
0
Order By: Relevance
“…In naturally infected mule deer, serine homozygosity at Prnp codon 225 seems to increase risk for CWD infection, as the probability that a CWD-infected animal was 225SS was 30 times greater than for S/F or FF when the frequency of genotypes was compared among CWD negative and positive deer (n = 1482 deer) [34]. As noted above, 225SF mule deer had a delay in the kinetics of experimental infection [17].…”
Section: The Cervid Prnp Genementioning
confidence: 86%
See 2 more Smart Citations
“…In naturally infected mule deer, serine homozygosity at Prnp codon 225 seems to increase risk for CWD infection, as the probability that a CWD-infected animal was 225SS was 30 times greater than for S/F or FF when the frequency of genotypes was compared among CWD negative and positive deer (n = 1482 deer) [34]. As noted above, 225SF mule deer had a delay in the kinetics of experimental infection [17].…”
Section: The Cervid Prnp Genementioning
confidence: 86%
“…In mule deer, PrP Sc is detectable in the retropharyngeal lymph node within only six weeks following an oral exposure [76]. In a further study of the kinetics of prion infection in mule deer, Fox et al showed that PrP Sc is widely distributed in lymphoid tissues by three months post-oral exposure when it is first detected in brain [17]. By nine months, PrP Sc was detected in the myenteric and submucosal plexi throughout the gastrointestinal tract and in the vagus nerve, and by 16 months, PrP Sc deposits were detectable throughout the brain and spinal cord.…”
Section: Cwd Prion Spread and Target Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…The probable causative agent of CWD is an abnormal prion protein (PrP CWD ). The course of CWD varies among animals and prion protein (Prnp) genotypes but averages approximately 2 yr from infection to death (Williams et al, 2002;Fox et al, 2006). In captive mule deer PrP CWD accumulates in lymph nodes about 1.5-3 mo after infection (Sigurdson et al, 1999) and roughly 6 mo later becomes detectable in the obex portion of the brainstem (Williams and Miller, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Within 10-12 mo after obex infection, clinical signs become apparent (Williams and Miller, 2002) including emaciation; loss of fear of humans; drooping head and ears; excessive drinking, urination, and salivation; dehydration; lethargy; and ataxia (Spraker et al, 1997;Williams, 2005). Once clinical signs appear, death occurs within a few weeks to 1 yr (Williams et al, 2002;Fox et al, 2006).…”
Section: Introductionmentioning
confidence: 99%